2018
DOI: 10.1002/brb3.946
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of paramedian pontine arteries disease and its association with hemoglobinA1c

Abstract: ObjectivesThe association of branch atherosclerotic disease (BAD) and diabetes mellitus (DM) in the territory of posterior circulation is rarely discussed. Intracranial BAD was divided into two different types: paramedian pontine arteries (PPA) disease (PPD) and lenticulostriate arteries (LSA) disease. The goal of the study was to evaluate the clinical characteristics of PPD and its association with hemoglobinA1c (HbA1c) in China.Materials and MethodsRadiologically confirmed PPD was defined as an isolated unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Meanwhile, multinomial logistic regression analysis depicted that the fasting blood glucose (FBG) level was an independent risk factor for BAD. These results are consistent with previous studies showing that DM or HbA1c is associated with BAD, especially paramedian pontine arteries disease (33).…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, multinomial logistic regression analysis depicted that the fasting blood glucose (FBG) level was an independent risk factor for BAD. These results are consistent with previous studies showing that DM or HbA1c is associated with BAD, especially paramedian pontine arteries disease (33).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the findings of other studies showing that vascular risk factors are more commonly associated with BAD than with LAA. [12,13] This retrospective study had a small sample size, with many patients who met the exclusion criteria. In addition, since the results were from a single tertiary care hospital, it may not be generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] Several studies have provided evidence suggesting that the lesion extended to the basal surface of the pons because of atherosclerosis-associated BAD. [12,13] Cerebral and peripheral arterial diseases (PAD) share atherosclerosis as a common mechanism. PAD is broadly defined as stenosis or aneurysm of the aorta and its branch arteries but is generally defined as stenosis of the lower extremity arteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes was associated more with SVO. Li et al found that patients with pontine infarction caused by SVO were more likely to have diabetes than those with SVO-induced nonpontine infarction in the anterior circulation [ 18 ]. Thus, we performed a further subgroup analysis of patients with SVO.…”
Section: Discussionmentioning
confidence: 99%